2018
DOI: 10.1002/aocs.12098
|View full text |Cite
|
Sign up to set email alerts
|

Formation of 4‐Hydroxy‐2‐Trans‐Nonenal, a Toxic Aldehyde, in Thermally Treated Olive and Sunflower Oils

Abstract: 4‐Hydroxy‐2‐trans‐nonenal (HNE) is a toxic aldehyde produced mostly in oils containing polyunsaturated fatty acid due to heat‐induced lipid peroxidation. The present study examined the effects of the heating time, the degree of unsaturation, and the antioxidant potential on the formation of HNE in two light olive oils (LOO) and two sunflower oils (one high oleic and one regular) at frying temperature. HNE concentrations in these oil samples heated for 0, 1, 3, and 5 hours at 185 °C were measured using high‐per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
(49 reference statements)
0
5
1
Order By: Relevance
“…Results reported from unoxidized unsaturated vegetable oils vary from 0.01 to 0.2 μg/g of oil, which are in agreement with our results. Levels reported in oxidized oils vary from 2.0 to 45 μg/g of oil. In one of the studies, oxidized rapeseed oil reached 4-HHE and 4-HNE levels of respectively 14 and 15 μg/g of oil after 11 days of storage of 28 g of oil in 1.1 L closed vessels in the dark at 37 °C, which are respectively about 5 and 15 times higher than our data. The other reported numbers (soybean, sunflower, palm, corn, linseed, camelina, and peanut oils) are much higher than in the present study, since these data are from studies of deep-frying of oils, which have been exposed to far higher temperatures (>180 °C).…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Results reported from unoxidized unsaturated vegetable oils vary from 0.01 to 0.2 μg/g of oil, which are in agreement with our results. Levels reported in oxidized oils vary from 2.0 to 45 μg/g of oil. In one of the studies, oxidized rapeseed oil reached 4-HHE and 4-HNE levels of respectively 14 and 15 μg/g of oil after 11 days of storage of 28 g of oil in 1.1 L closed vessels in the dark at 37 °C, which are respectively about 5 and 15 times higher than our data. The other reported numbers (soybean, sunflower, palm, corn, linseed, camelina, and peanut oils) are much higher than in the present study, since these data are from studies of deep-frying of oils, which have been exposed to far higher temperatures (>180 °C).…”
Section: Discussioncontrasting
confidence: 65%
“…Results reported from unoxidized unsaturated vegetable oils vary from 0.01 to 0.2 µg/g oil 40 , which are in agreement with our results. Levels reported in oxidized oils vary from 2.0 to 45 µg/g oil [40][41][42][43] . In one of the studies 40 , oxidized rapeseed oil reached HHE and HNE levels of respectively 14 µg/g and 15 µg/g oil after 11 days storage of 28 grams oil in 1.1 litre closed vessels in dark at 37 °C, which are respectively about 5 and 15 times higher than our data.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent reports showed that the total amount of GO, MGO, and 2,3-BD formed 55- and 15-fold in heated butter and margarine (from 100 to 200°C), and the volatiles were increased with the temperature and constant with time in olive oils ( 5 , 12 ). The content of 4-HNE was increased in the sunflower oil (185°C for 5 h) rich in linoleic acid (LA) and was more susceptible to decomposition ( 13 ). The close relationship between the UFAs and their corresponding volatile aldehydes was also revealed by some studies ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of previous experiments by the author have shown the formation of HNE due to heat treatments in various oils [34]- [39]. HNE has also been shown to incorporate into fried food [40] [41].…”
Section: Introductionmentioning
confidence: 96%